2004
DOI: 10.1128/aem.70.3.1397-1404.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Thermostable l -Arabinose ( d -Galactose) Isomerase from the Hyperthermophilic Eubacterium Thermotoga maritima

Abstract: The araA gene encoding L-arabinose isomerase (AI) from the hyperthermophilic bacterium Thermotoga maritima was cloned and overexpressed in Escherichia coli as a fusion protein containing a C-terminal hexahistidine sequence. This gene encodes a 497-amino-acid protein with a calculated molecular weight of 56,658. The recombinant enzyme was purified to homogeneity by heat precipitation followed by Ni 2؉ affinity chromatography. The native enzyme was estimated by gel filtration chromatography to be a homotetramer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 30 publications
5
121
0
Order By: Relevance
“…As previously reported, it was found that the metal dependence of the AIs increased with the temperature at which they were assayed [20,21]. To further characterize this aspect, we analysed the decrease in enzyme activity of the apo and holo proteins at various GdnHCl concentrations (Fig.…”
Section: +mentioning
confidence: 98%
See 3 more Smart Citations
“…As previously reported, it was found that the metal dependence of the AIs increased with the temperature at which they were assayed [20,21]. To further characterize this aspect, we analysed the decrease in enzyme activity of the apo and holo proteins at various GdnHCl concentrations (Fig.…”
Section: +mentioning
confidence: 98%
“…Recombinant AIs were purified as described elsewhere [20,21]. The purified AIs were dialyzed against 10 mM Tris-HCl buffer [pH 7.0 except with B. halodurans (BHAI) at pH 8.0] and stored at 4°C.…”
Section: Expression and Purification Of Aismentioning
confidence: 99%
See 2 more Smart Citations
“…Having overcome these problems, other conversion-related enzymes including D-xylose isomerase (XylA), [22] RhaD [23] and AphA [18] from Escherichia coli, L-arabinose and Dgalactose isomerase (AraA) from Thermotoga maritima MSB8, [24] DTE from Pseudomonas Sp, St-24 [11] were prepared as described in supporting information.…”
mentioning
confidence: 99%